IMPROVING COMMUNITY WELFARE THROUGH RENEWABLE ENERGY BASED DEVELOPMENT - Ardiansyah, Adi; Jasmine, Veronika Joan (LPPM Universitas Bina Bangsa, 2025)
Improving community wells is a key goal of sustainable development. The way to achieve this is the development of renewable energy. In this context, development does not only focus on providing environmentally friendly energy sources, but also seeks to improve the quality of life in our communities. The aim of this research is to investigate the positive effects of applying renewable energy technologies such as solar energy, wind power, and biomass for people's wells in various regions in Indonesia. The methodology used includes secondary data analysis and case studies in fields where renewable energy projects have been implemented. The research results show that investment in renewable energy contributes to job creation, reduces poverty and increases access to cheaper and more sustainable energy. In addition, the development of renewable energy infrastructure has important social implications, such as improving education and public health. The conclusions of this research support the importance of collaboration between government, the private sector and communities to promote investment in renewable energy as a strategic step to increase wells throughout society.